BMP6 and VDR gene polymorphisms are associated with osteonecrosis in a sickle cell anaemia cohort - Arcanjo, Gabriela S.; Souza, Mariana B.; Domingos, Igor F.; Pereira‐Martins, Diego A.; Falcão, Diego A.; Batista, Jessica V.; Hatzlhofer, Betania L.; Diniz, Madi V.; Silva, Alexsandro P.; Guaraná, Werbson L.; Hazin, Manuela F.; Araujo, Aderson S.; et al. (British journal of haematology, 2024)
Summary The occurrence and severity of osteonecrosis in sickle cell anaemia (SCA) vary due to risk factors, including genetic modifiers. Bone morphogenetic proteins (BMPs), particularly BMP6, and the vitamin D receptor (VDR) play key roles in cartilage and bone metabolism, making them potential contributors to orthopaedic outcomes in SCA. Here, we evaluated the association of polymorphisms in BMP6 (rs3812163, rs270393 and rs449853) and VDR (FokI rs2228570 and Cdx2 rs11568820) genes with osteonecrosis risk in a Brazilian SCA cohort. A total of 177 unrelated SCA patients were selected. The AA genotype of BMP6 rs3812163 was independently associated with a lower osteonecrosis risk (p = 0.015; odds ratio (OR): 0.38; 95% confidence interval (CI): 0.18–0.83) and with the long‐term cumulative incidence of osteonecrosis (p = 0.029; hazard ratio: 0.56, 95% CI: 0.34–0.94). The VDR rs2228570 TT genotype was independently associated with a lower osteonecrosis risk (p = 0.039; OR: 0.14; 95% CI: 0.02–0.90). In summary, our results provide evidence that BMP6 rs3812163 and the VDR rs2228570 might be implicated in osteonecrosis pathophysiology in SCA and might help identify individuals at high risk. The occurrence and severity of osteonecrosis in sickle cell anaemia (SCA) vary due to diverse risk factors, including frequent vaso‐occlusive crises, lower haemoglobin fetal levels and genetic modifiers. Bone morphogenetic proteins (BMPs), particularly BMP6, and the vitamin D receptor (VDR) play key roles in cartilage and bone metabolism, making them potential contributors to orthopaedic outcomes in SCA. Here, we examined the association between candidate single nucleotide polymorphisms in BMP6 (rs3812163, rs270393, and rs449853) and VDR (rs2228570 and rs11568820) genes with the development of osteonecrosis in a Brazilian SCA cohort. Our findings confirmed the associations of BMP6 rs3812163 polymorphism with a reduced risk of osteonecrosis. Additionally, we observed that the functional VDR FokI polymorphism was associated with reduced risk of osteonecrosis. Collectively, these results provide evidence that variants in genes related to bone metabolism and cartilage development may be linked to osteonecrosis risk in SCA.